Making Invisible Monuments Visible - Balakrishnan, Gita; Ambe, Sonam; Kumar, Rasya (MAJ - Malaysia Architectural Journal, 2025)
A monument is defined as a historically significant building commemorating a person/event. This perpetuates social injustice since monuments thus defined often record the history of a privileged minority. Common people could not access the palaces, forts and religious structures that we today list as monuments. Architecture must be equal in its narration of history. We know in detail how royalty lived, prayed, won wars, relaxed and were laid to rest. However, the principles and techniques of construction that we learn from grand edifices are not typically employed in the construction for the majority. In our veneration of monuments, we need to dig deeper to study the homes of the forgotten many, the structures that they built and interacted with on a daily basis. These ‘invisible monuments’ tell the story of the commons giving us a glimpse into their lives, their context and their history. Their native intelligence resulted in “living museums” of their craftsmanship. After all, the epitome of human civilisation - the Indus Valley - was not a luxurious abode of one but a fine example of architecture and town planning where over 5 million people thrived. A survey to establish people’s notion of monuments along with the learnings from the first author’s four extensive expeditions totalling over 2500 km on foot across the country titled - Walk for Arcause - Kolkata to Delhi, Kolkata to Dhaka, Konark to Bhubaneswar and Chennai to Bangalore have established the urgent need for documentation of vernacular and traditional practices through collective action. Clear possible action points will be elucidated as replicable models to create open-source repositories of these invaluable invisible monuments.